Solution to a New Variant of the Assignment Problem Using Cohort Intelligence Algorithm - Krishnasamy, Ganesh; Kulkarni, Anand Jayant; Abraham, Ajith (Cohort Intelligence: A Socio-inspired Optimization Method, 2017)
In this chapter, we present a variant of the classical assignment problem (Kulkarni et al. in European Journal of Operational Research, 250(2):427–447, 2016, [1]). The model has applications in healthcare systems and inventory management. The problem stems from an application in healthcare management. Specifically, a surgical scheduling in a hospital setting is a complex combinatorial problem. In addition, similar problem arises in minimizing the space requirements in a retail store.